Positioning QRIS Within Global Retail Payment Systems: Comparative and Regulatory Perspectives - Dian Fitriarni Sari; Dwi Bayinah Wulandari; Innaniar Kultsum (LPPM Universitas KH A. Wahab Hasbullah, 2026)
The transformation of digital payment systems is driving cross-border transactions. This study analyses the position of QRIS as Indonesia’s national digital payment standard within the global landscape of retail payment systems, using qualitative methods with a comparative and regulatory approach. This approach is employed to compare the regulatory structure, operational model and governance of QRIS with other global payment systems. The main variables in this study include the regulatory framework for payment systems, transaction cost efficiency, system interoperability, cross-border settlement mechanisms, digital and regulatory sovereignty, and cross-jurisdictional supervisory integration. This study contributes to the literature on how QRIS is strategically positioned within the dynamics and structure of the international payment system as a national QR-based payment standard, and expands cross-border schemes through Regional Payment Connectivity and Local Currency Transactions. QRIS has the potential to serve as a strategic alternative to global infrastructure through cost efficiency, high interoperability, and local currency-based settlement.